Gray Matter Abnormalities in Myotonic Dystrophy Type 1: A Voxel-Wise Meta-Analysis - Jiang, Qirui; Lin, Junyu; Li, Chunyu; Hou, Yanbing; Shang, Huifang (Frontiers in Neurology, 2022)
Background: A growing number of voxel-based morphometry (VBM) studies have demonstrated widespread gray matter (GM) abnormalities in myotonic dystrophy type 1 (DM1), but the findings are heterogeneous. This study integrated previous VBM studies to identify consistent GM changes in the brains of patients with DM1. Methods: Systematic retrieval was conducted in Web of Science, Pubmed, and Emabase databases to identify VBM studies that met the inclusion requirements. Data was extracted. The Seed-based d Mapping with Permutation of Subject Images (SDM-PSI) software was used for meta-analysis of voxel aspects. Results: A total of 8 VBM studies were included, including 176 patients with DM1 and 198 healthy controls (HCs). GM volume in patients with DM1 was extensively reduced compared with HCs, including bilateral rolandic operculum, bilateral posterior central gyrus, bilateral precentral gyrus, right insula, right heschl gyrus, right superior temporal gyrus, bilateral supplementary motor area, bilateral middle cingulate gyrus/paracingulate gyrus, left paracentral lobule, and bilateral caudate nucleus. Meta-regression analysis found that regional GM abnormalities were associated with disease duration and ROCF-recall scores. Conclusion: DM1 is not only a disease of muscle injury, but also a multi-system disease involving brain motor and neuropsychiatric regions, providing a basis for the pathophysiological mechanism of DM1.